An evaluation of the tablet armchair in selected public schools based on the principles of Ergonomics - Sula, Regina Maye R.; Gallardo, Mildred (Quezon City College of Home Economics, University of the Philippines Diliman, 2018)
Students spend a considerable amount of time doing school work while being seated on their chairs. Numerous studies have found that school children experience musculoskeletal pain due to inadequately designed school chairs. To give insight on the current status of public elementary school seating furniture, the study recorded the chair experiences of 12 student respondents (N=12) in Grades V-VI from two schools in District IV of Manila. The Study focused on the evaluation of the wood and metal type of tablet armchair variations present in both schools. Anchored on the principles of ergonomics and user-centered design, the study aimed to understand the correlation between the user, the task, and the product in order to draw design considerations for an ideal public elementary chair design. The multi-method study employed postural analysis through participant observation and subjective comfort evaluation through one-on-one interviews. Anthropometric data and chair dimensions relevant to chair design were recorded and compared using biomechanics principles in order to assess the suitability of the chairs to the users. Results showed that mismatch existed between the respondents and their assigned tablet armchairs, causing majority of them to experience musculoskeletal pains, mainly on four body parts; the neck (8/N), upper back (9/N), lower back (6/N), and buttocks (8/N). Aside from recording their discomforts, the study also noted the respondents' coping mechanisms as well as their ideal chair preferences. The research concluded that school seating furniture design must consider the following: (1) size based on the 5th or 95th percentile of recent anthropometric data, (2) adjustability, (3) form, (4) materiality, (5) finish, and (6) additional support on the elbows and lower back.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: User-centered system design; Armchairs